ÅCómo debe intervenir la arquitectura para que la Estación de la Sabana se convierta en una pieza urbana integrada a la ciudad? (2017)
This project has the purpose to integrate the old Sabana train Station with the current city and conditions. In order to do this, there are going to go in play several strategies that will give solutions to the different problems, both urban and architectonic. The strategies are going to be: reactivation of the area, restoration and conditioning of the old buildings to new uses.--Tomado del Formato de Documento de Grado.